Optimization of Enzymatic Hydrolysis by Protease Produced from Bacillus subtilis MTCC 2423 to Improve the Functional Properties of Wheat Gluten Hydrolysates - Hari Prasath Rajendhran; Vinoth Kumar Vaidyanathan; Swethaa Venkatraman; Pothiyappan Karthik (International Journal of Food Science)
This study is aimed at investigating the reutilizing of gluten protein from the wheat processing industry by Bacillus subtilis MTCC 2423 protease to obtain gluten hydrolysates with high added value. Gluten protein hydrolysis using protease achieved a 34.07% degree of hydrolysis with 5% gluten protein, at a hydrolysis time of 2 h for 1000 U/mL at pH 8.0 and temperature of 40°C. Compared to the wheat gluten, the obtained hydrolysates exhibited enhanced functional attributes, including heightened solubility (43%), increased emulsifying activity (93.08 m2/g), and improved radical scavenging properties. Furthermore, these hydrolysates demonstrated enhanced antioxidant potential, as evidenced by elevated ABTS (2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) of 81.25% and DPPH (2,2-diphenyl-1-picrylhydrazyl) of 56.46% radical scavenging activities and also exhibited a higher α-amylase inhibitory effect of 33.98%. The enhancement in functional characteristics of wheat gluten hydrolysates was observed by Fourier transform infrared spectroscopy. The percentage of free amino acids obtained by protease-mediated hydrolysates increased significantly compared to the unhydrolyzed wheat, which was observed by high-performance liquid chromatography. These findings suggest that wheat gluten hydrolysates hold promising potential as functional and nutritional food ingredients in the food industry, owing to their enhanced functionalities and potential antioxidant and antidiabetic properties.